2019
DOI: 10.4143/crt.2018.262
|View full text |Cite
|
Sign up to set email alerts
|

Early Decline in Left Ventricular Ejection Fraction Can Predict Trastuzumab-Related Cardiotoxicity in Patients with Breast Cancer: A Study Using 13 Years of Registry Data

Abstract: The overall incidence of TRCD was 7.4% in Asian breast cancer patients treated with adjuvant trastuzumab. A decline in LVEF ≥5% within the first 3 months of trastuzumab initiation was strongly associated with TRCD development in patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In the present study, the cumulative dose of anthracyclines, baseline LVEF and DC was revealed as independent risk factors of trastuzumab‐related cardiotoxicity. In agreement with previous data, 10,11 univariate and multivariate analyses in the present study showed that a high cumulative dose of anthracyclines was a risk factor for trastuzumab‐related cardiotoxicity. The cardiotoxicity of anthracyclines is an indisputable fact; however, due to the positive efficacy of anthracyclines in chemotherapy for breast cancer, 12 they are still widely used in clinical practice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the cumulative dose of anthracyclines, baseline LVEF and DC was revealed as independent risk factors of trastuzumab‐related cardiotoxicity. In agreement with previous data, 10,11 univariate and multivariate analyses in the present study showed that a high cumulative dose of anthracyclines was a risk factor for trastuzumab‐related cardiotoxicity. The cardiotoxicity of anthracyclines is an indisputable fact; however, due to the positive efficacy of anthracyclines in chemotherapy for breast cancer, 12 they are still widely used in clinical practice.…”
Section: Discussionsupporting
confidence: 93%
“…Currently, there is accumulating evidence that low baseline LVEF is an objective predictor of trastuzumab treatment‐related cardiotoxicity, even when the baseline LVEF was within the normal range 10,15 . However, a uniform threshold has not been established due to the heterogeneity of the study populations.…”
Section: Discussionmentioning
confidence: 99%
“…A large analysis with 13 years of follow-up recently addressed this often overlooked issue. The authors focused on the implications of an early, asymptomatic LVEF drop on the subsequent development of significant or symptomatic cardiac toxicity [10]. In 337 out of 787 patients, a 5% or more LVEF loss from baseline occurring within the initial 3 months of trastuzumab treatment was predictive of the development of either a significant, asymptomatic reduction in LVEF or of congestive heart failure, which occurred in 5% and 2.3% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Other echocardiography parameters, such as myocardial performance index (MPI), which can identify subclinical cardiotoxicity in patients treated with 5-FU and anthracyclines, and mitral annular plane systolic excursion (MAPSE), may also be used [ 83 , 84 ]. LVEF <55% was associated with a significantly increased risk to develop HF, due to HER2 antagonists and anthracyclines [ 85 , 86 ].…”
Section: Diagnosis Methods Of Chemotherapy-induced Cardiotoxicity In Gi Cancersmentioning
confidence: 99%